The Effectiveness of Using Audio Visual Media in Information Services to Improve Students' Understanding of Sex Education at SMKN 4 Sijunjung - Hesti Sefriyani; Mori Dianto; Wira Solina (Universitas Negeri Padang, 2022)
This research is motivated by the existence of students who are less aware of the importance of sex education in everyday life. The purpose of this study is to describe: 1) An overview of students' understanding of sex education before being given information services using audio-visual media. 2) Description of students' understanding of sex education after being provided with information services using audio-visual media. 3) The effectiveness of information services using audio-visual media in improving students' understanding of sex education. This research is a pre-experimental design research (Nondesign One Group). The population in this study were 147 students and the sample was 31 students using purposive sampling technique. The instrument used is a questionnaire. Meanwhile, for data analysis using percentage and t-test formula. Based on the results of research on the effectiveness of information services using audio-visual media to improve students' understanding of sex education, the following conclusions can be drawn: 1) The description of students' understanding of sex education before being given information services using audio-visual media is in the low category. 2) The description of the sex education of students after being provided with information services using audio-visual media is in the very high category. 3) The significance of the effectiveness of information services using audio-visual media to improve the understanding of sex education of students at SMKN 4 Sijunjung. Based on the results of this study, it is recommended for BK teachers to help students through information services using audio-visual media so that they can improve students' understanding of sex education.